2015
DOI: 10.1016/j.rpped.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do aleitamento materno sobre a obesidade em escolares: influência da escolaridade da mãe

Abstract: Objective:To evaluate the association between duration of breastfeeding (BF) and obesity in schoolchildren of Florianópolis (SC), and the role of possible effect modifiers.Methods:Cross-sectional study with a random sample of 2826 schoolchildren (7-14 years). Weight and height were measured according to standardized procedures. Data concerning BF and sociodemographic variables were obtained from a questionnaire sent to parents/guardians. Children's nutritional status was evaluated by BMI-for-age z-score for ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(50 reference statements)
0
7
0
3
Order By: Relevance
“…Na sequência surge o DSC 4, que revela que as profissionais conhecem e vivenciam a importância do aleitamento materno, pois a prática evita o aparecimento de várias doenças e, principalmente, pode evitar cerca de 820.000 mortes todo o ano (14) , além de atuar como agente tranquilizador da criança no aspecto psicológico, auxiliando na promoção do desenvolvimento intelectual (16) . Quanto aos prejuízos em curto prazo causados pelo desmame precoce, destaca-se a baixa imunidade da criança, que poderá favorecer as morbidades, tais como: infecções comuns, alergias, diarréia, doenças respiratórias, desnutrição, entre outras, e predispõem a morbidades em longo prazo, tais como: hipertensão, colesterol alto, obesidade e diabetes do tipo 2 (13,14,(17)(18)(19) .…”
Section: Ideias Centraisunclassified
“…Na sequência surge o DSC 4, que revela que as profissionais conhecem e vivenciam a importância do aleitamento materno, pois a prática evita o aparecimento de várias doenças e, principalmente, pode evitar cerca de 820.000 mortes todo o ano (14) , além de atuar como agente tranquilizador da criança no aspecto psicológico, auxiliando na promoção do desenvolvimento intelectual (16) . Quanto aos prejuízos em curto prazo causados pelo desmame precoce, destaca-se a baixa imunidade da criança, que poderá favorecer as morbidades, tais como: infecções comuns, alergias, diarréia, doenças respiratórias, desnutrição, entre outras, e predispõem a morbidades em longo prazo, tais como: hipertensão, colesterol alto, obesidade e diabetes do tipo 2 (13,14,(17)(18)(19) .…”
Section: Ideias Centraisunclassified
“…Considering schoolchildren whose mothers have a higher education level, the chance of obesity was 44% lower for those who were breastfed for more than twelve months. 9 Another study conducted in Florianópolis in 2012/2013 on schoolchildren found a significant association between excess body fat (measured by the skinfold thickness) and exclusive breastfeeding until the sixth month of life. 10 Studies related to such theme with the same age group conducted in Brazil have shown similar results; however, some associated any period of BF with lower levels of obesity; conversely, others showed an association of a higher duration of BF and outcomes related to obesity in some specific strata (age/maternal schooling).…”
Section: Introductionmentioning
confidence: 98%
“… 10 Studies related to such theme with the same age group conducted in Brazil have shown similar results; however, some associated any period of BF with lower levels of obesity; conversely, others showed an association of a higher duration of BF and outcomes related to obesity in some specific strata (age/maternal schooling). 8 , 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…Nutritional values of breast milk also have a beneficial role in both short and long-term neurological development [ 12 , 13 , 14 ], and exposure to breast milk antigens promotes the development of tolerance and significantly reduces the risk of allergy and atopic diseases [ 15 , 16 ]. However, the long-term benefits of breast milk on the prevention of leukaemia [ 17 ], obesity [ 18 ], type 2 diabetes [ 19 ], and others are not yet fully assessed.…”
Section: Introductionmentioning
confidence: 99%